2013
DOI: 10.1007/978-3-642-36763-2_2
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Network Exploration to Derive Insights: Filtering, Clustering, Grouping, and Simplification

Abstract: Abstract. The growing importance of network analysis has increased attention on interactive exploration to derive insights and support personal, business, legal, scientific, or national security decisions. Since networks are often complex and cluttered, strategies for effective filtering, clustering, grouping, and simplification are helpful in finding key nodes and links, surprising clusters, important groups, or meaningful patterns. We describe readability metrics and strategies that have been implemented in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
0
18
0
1
Order By: Relevance
“…In NodeXL, 5 different clusters (subgroups) are marked with different colors. The connotations of keywords are therefore explored through the cluster analysis Shneiderman and Dunne 2012;Himelboim et al 2013), whereas the shifts of policy priorities are observed through analyzing the changes in keywords of high degree centrality.…”
Section: Methodsmentioning
confidence: 99%
“…In NodeXL, 5 different clusters (subgroups) are marked with different colors. The connotations of keywords are therefore explored through the cluster analysis Shneiderman and Dunne 2012;Himelboim et al 2013), whereas the shifts of policy priorities are observed through analyzing the changes in keywords of high degree centrality.…”
Section: Methodsmentioning
confidence: 99%
“…NodeXL [44,45], as a Microsoft Excel plug-in for the creation of node-link diagrams, is accessible to a broader audience. NodeXL lets users specify mappings from data attributes to several visual variables.…”
Section: Authoring Graph Visualizationsmentioning
confidence: 99%
“…Fourth, we would like to customize the technique of representing a set of individuals with attached frequencies and proximities as a rectangular map to detect communities in graphs, [21], by analyzing the adjacencies represented in the rectangular map. Finally, our method can also be applied to visualize hierarchical data, in which inside every rectangle a new rectangular map has to be represented by taking into account adjacencies with neighboring rectangles and its inner rectangular maps, [12,27,48]. However, the mathematical optimization treatment of these extensions is not trivial and thus further research is still needed.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%